The Olympic Games : a critical approach - Jefferson Lenskyj, Helen (SocietyNow., 2020)
Do the Olympic Games really live up to their glowing reputation? As the biggest global sport mega-event, the Olympic Games command public and media attention, while Olympic mythology and ritual obscure their underlying function as a profit-making business enterprise.